Nutrient-Dense Moringa oleifera Leaf Supplementation Increases Human Milk Output in Western Kenyan Mothers. (14th June 2022) - Attia, Suzanna; Mbullo, Patrick; Mogaka, Jerusha; Odhiambo, Silvia; McGuire, Michelle; Fuchs, George; Waterman, Carrie
Abstract: Objectives: We aim to evaluate the impact of moringa leaf powder on maternal and infant nutrition, milk output, and intestinal health. Methods: This was a single-blinded cluster-randomized controlled trial of 20g of moringa in corn porridge versus porridge alone taken daily for 3 months by exclusively breastfeeding women of term infants (>36 weeks gestational age) enrolled within 30 days of birth in Kisumu, Kenya. At enrollment and exit, we collected 24-hour pumped milk output, milk, maternal and infant fecal and capillary samples, and Hemoglobin by HemoCue©. We performed monthly infant and maternal anthropometrics. We will perform biosample analysis for markers of vitamin A and iron status, IGF-1, and inflammatory markers; milk/fecal microbiome; milk composition; and intestinal inflammation/markers of environmental enteric dysfunction. Data is analyzed via IBM SPSS v.27 with univariate and multivariate analysis for primary and secondary outcomes. Results: N = 50 mother-infant pairs (infants 44% female). Most infants were appropriate for gestational age (GA) (27, 54%) with 19 (38%) large for GA and 1 small for GA. Mothers' were initially 14% wasted (MUAC < 23cm),  with MUAC 26.2 ± 2.7cm overall,  n = 49. Wasting resolved in all. Maternal 24-hour milk output did not differ at enrollment between clusters (502.5, 303.8–896.3, n = 24 vs. 525.0, 363.8–693.8 mL, n = 24; p = 1.0) but did increase dramatically at exit in the cluster receiving moringa (control: 648.81 ± 324.1,  n = 21 vs. intervention: 981.09 ± 368.3 mL,  n = 23; p = 0.003). Infant growth (average daily weight gain, total weight gain, WLZ, WAZ, or LAZ) and maternal MUAC and BMI did not differ between clusters at enrollment or exit. Maternal and infant hemoglobin (hgb) did not differ between clusters at enrollment; maternal anemia (hgb < 11 g/dL) trended higher in the control at enrollment (40% vs. 12.5%, n = 49, p = 0.05); at exit this difference resolved. Infant hgb was higher at exit in the intervention group (11.3 ± 0.8 vs. 10.7 ± 1.0,  p = 0.02). No participants experienced adverse effects. Conclusions: 20g daily moringa leaf powder for three months increases maternal milk output but has no impact on growth in a sample of Kenyan infants and mothers with a low rate of initial undernutrition. Funding Sources: This research was funded by an NIH K award and an NIH BIRCWH Award as well as early investigator startup funds from the University of Kentucky.